The heavy economic toll of gender-based violence - Ouedraogo, Rasmane,Stenzel, David (International Monetary Fund, 2021)
The COVID-19 pandemic and lockdowns have led to a rise in gender-based violence. In this paper, we explore the economic consequences of violence against women in sub-Saharan Africa using large demographic and health survey data collected pre-pandemic. Relying on a two-stage least square method to address endogeneity, we find that an increase in the share of women subject to violence by 1 percentage point can reduce economic activities (as proxied by nightlights) by up to 8 percent. This economic cost results from a significant drop in female employment. Our results also show that violence against women is more detrimental to economic development in countries without protective laws against domestic violence, in natural resource rich countries, in countries where women are deprived of decision-making power and during economic downturns. Beyond the moral imperative, the findings highlight the importance of combating violence against women from an economic standpoint, particularly by reinforcing laws against domestic violence and strengthening women's decision-making power
10.5089/9781557754073.001
Keywords: Graue Literatur; Gender-based violence; economic development; sub-Saharan Africa; Domestic Abuse; Economics of Gender; Family Structure; Marital Dissolution; Marriage; Gender Studies; Econometrics; Women''s Studies'; Macroeconomics; Economics: General; Non-labor Discrimination; Household Production and Intrahousehold Allocation; Economic Development: General; Education: General; Unemployment; Wages; Intergenerational Income Distribution; Aggregate Human Capital; Aggregate Labor Productivity; Estimation; Agricultural and Natural Resource Economics; Environmental and Ecological Economics: General; Economic & financial crises & disasters; Economics of specific sectors; Gender studies; women & girls; Labour; income economics; Econometrics & economic statistics; Social discrimination & equal treatment; Gender; Employment; Labor; Estimation techniques; Econometric analysis; Gender inequality; Currency crises; Informal sector; Economics; Women; Education; Employment; Economic theory; Econometric models; Sex discrimination